Peningkatan hasil belajar siswa kelas IV pada pembelajaran IPS dengan menggunakan model Learning Starts with a question di SDN 14 Siguntur Muda Kecamatan Koto XI Tarusan Pesisir Selatan - Syefnidar Syefnidar (JPGI (Jurnal Penelitian Guru Indonesia), 2018)
This research is motivated by the low of IPS study a result of fourth graders of SDN 14 Siguntur Muda Kecamatan Koto XI Tarusan. The purpose of the study was to describe the improvement of students' IPS learning outcomes with the Learning Starts With A Question Model. The type of research is Classroom Action Research (PTK) which is implemented in two cycles. The data source is the fourth grader of 17 students. The instruments used are students 'affective field assessment sheets, teacher activity sheets and students' comprehension tests. Based on the results of the analysis of the affective domain of students is to write questions and make summaries. Percentage of writing questions and making a summary of each cycle has increased. From the data obtained can be concluded that there is an increase of learning outcomes IPS fourth-grade students SDN 14 Siguntur Muda District Koto XI Tarusan after using Learning Starts With A Question model.